Remote measurement and control apparatus - ZHAO YUN; SHI XIAOMENG; REN XIAOFENG; ZHU DELIANG; LI LIN; WANG LINING; ZHENG DANFENG; SHAO SHANSHAN (2016)
The utility model provides a pair of remote measurement and control apparatus, including power module, processor module, storage module, communication module, collection module and interaction module, power module provide power supply for whole device, processor module include LPC1768 microprocessor and outlying crystal oscillator circuit, storage module, communication module, collection module and interaction module be electrically connected to on the processor module respectively. On monitoring cost and the basis that reduces the consumption, can parallel running communication task, data acquisition task, mutual task, storage task, the soft task that resets, satisfy the requirement that most remote data observed and controled.